Peningkatan Keterampilan Membaca Puisi Melalui Metode Modeling - Aniria Zebua (JURNAL GLOBAL EDUKASI, 2020)
Abstract: The purpose of the research in accordance with the above problem formulation through modeling can improve the quality of learning in terms of improving teacher skills, student activities and students' skills Class II/b SDN 075019 Dahana Tabaloho. The research subjects were teachers and students of Class II/b of SD Negeri 075019 Dahana Tabaloho in the academic year 2018/2019, with 31 students consisting of 16 male students and 15 female students. The research variables are teacher skills, student activities and student skills outcomes. The study lasted 2 cycles. The data used is comparative descriptive analysis data by comparing the results of the first cycle and second cycle research. The results of this study indicate that the teacher's skills, student activities and students' skills in reading poetry. Cycle I average teacher skills 69 with a good category, cycle II 81 with a very good category. While the activity of cycle I students gained 72% in the good category, cycle II gained 76% in the good category. Overall results of teacher skills and student activities are good. Students' skills in reading poetry and the results of formative test cycle I obtained an average value of 66 with 58% classical completeness, cycle 2 gained an average of 76 with 84% classical completeness. Keywords: modeling, poetry reading, learning quality.  Abstrak: Tujuan dari penelitian sesuai dengan rumusan masalah diatas melalui modeling dapat meningkatkan kualitas pembelajaran dalam hal meningkatkan keterampilan guru, aktivitas siswa dan keterampilan siswa Kelas II/b SD Negeri 075019 Dahana Tabaloho. Subjek penelitian adalah guru dan siswa Kelas II/b SD Negeri 075019 Dahana Tabaloho tahun pelajaran 2018/2019, dengan jumlah siswa 31 terdiri dari 16 siswa laki-laki dan 15 siswa perempuan. Variabel Penelitian yaitu keterampilan guru, aktivitas siswa dan hasil keterampilan siswa. Penelitian berlangsung 2 siklus. Data yang digunakan data analisis deskriptif komperatif dengan mem bandingkan hasil penelitian siklus I dan siklus II. Hasil  penelitian  ini  menunjukkan  bahwa  keterampilan  guru,  aktivitas siswa dan keterampilan siswa dalam membaca puisi. Siklus I rata-rata keteram pilan guru 69 dengan kategori baik, siklus II 81 dengan kategori sangat baik. Sedangkan aktivitas siswa siklus I memperoleh 72% dengan kategori baik, siklus II memperoleh 76% dengan kategori baik. Hasil secara keseluruhan keterampilan guru dan aktivitas siswa sudah baik. Keterampilan siswa dalam membaca puisi dan hasil tes formatif siklus I memperoleh nilai rata-rata 66 dengan ketuntasan klasikal 58%, siklus 2 memperoleh rata-rata 76 dengan ketuntasan klasikal  84%. Kata  Kunci : modeling, membaca puisi, kualitas pembelajaran.